History teachers' perception of ICT in promoting teaching and learning - Amengor, Jonathan (University of Cape Coast, 2011)
Ghana, through her I.C.T. for Accelerated Development (ICT4AD) policy, has provided a number of ICT equipments to some schools in order to promote the integration of ICT into the teaching and learning process. This research study sheds light on Historyteachers’ perception and use of ICT tools in Senior High schools, by considering various variables which affect the success of the implementation of these tools. A questionnaire was completed by 67 History teachers who teach in Senior High Schools in both Kumasi and Cape Coast metropolis. Two hypotheses were formulated and tested at 0.5 significance level using SPSS version 16. The results showed that although History teachers are willing to use ICT resources and are aware of the existing potentials, they are facing problems in relation to accessibility to ICT resources and lack of in-service training opportunities.The hypothesis tested proved that there was no statistically significant difference between males and females history teachers perception of ICT. It further showed that there was nostatistically significant difference between those who have their personal computer and those who lack it. It is recommended that the government, through the Ministry of Education, provides schools and teachers with computers and other ICT infrastructure. Again, training opportunities should be made available for History teachers to familiarize themselves with skills of integrating ICT into their professional task.
ix, 101p.:ill
Keywords: ICT in teaching and learning; Information and Communication Technology; History teacher; ICT equipment; ICT infrusture; Computer uses; ICT tools